Development and characterization of an allergic asthma rat model for interventional studies - Périz M. (2020)
Allergic asthma is one of the most common chronic diseases of the airways, however it still remains underdiagnosed and hence undertreated. Therefore, an allergic asthma rat model would be useful to be applied in future therapeutic strategy studies. The aim of the present study was to develop an objective model of allergic asthma in atopic rats that allows the induction and quantification of anaphylactic shock with quantitative variables. Female Brown Norway rats were intraperitoneally sensitized with ovalbumin (OVA), alum and Bordetella pertussis toxin and boosted a week later with OVA in alum. At day 28, all rats received an intranasal challenge with OVA. Anaphylactic response was accurately assessed by changes in motor activity and body temperature. Leukotriene concentration was determined in the bronchoalveolar lavage fluid (BALF), and total and IgE anti-OVA antibodies were quantified in blood and BALF samples. The asthmatic animals’ motility and body temperature were reduced after the shock for at least 20 h. The asthmatic animals developed anti-OVA IgE antibodies both in BALF and in serum. These results show an effective and relatively rapid model of allergic asthma in female Brown Norway rats that allows the quantification of the anaphylactic response.